Implications for the Physical Design of the Postnatal Care Unit from a Targeted Analysis of Issues With Accessing the Bathroom at Night in the Acute Setting: A Secondary Analysis. Issue 1 (June 2021) - Chirumamilla, Varshita; Gerard, Joseph M.; Sweeney, Alison E.; Tully, Kristin P.; Stuebe, Alison M.; Patterson, Emily S.
Assessing hospital environment conditions is necessary for healthcare providers and patients to coordinate safe care. The aims of this research included: a) identifying patterns in hospital visit feedback transcripts regarding bathroom doors and lights in the hospital room and b) interpreting the results to make recommendations for more enabling clinical environments. The methods used by the research team included organizing transcript data, assigning codes, and conducting an interrater reliability test to assess codebook efficacy. Finally, working with maternal and infant mortality experts, recommendations for the hospital were developed. We identified four possible interventions to address barriers: a) implement low-height, dimmable lighting along the base of the patient room, b) provide personal lights, such as penlights, to staff for nighttime assessments, c) install and improve on existing grab bars in patient room bathrooms and d) replace the standard patient room bathroom door with a different kind of auditory/visual privacy barrier.